(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Standard precautions are essential in preventing healthcare-associated infections, yet compliance among nursing students often varies. Assessing their knowledge and practices is crucial for guiding educational and institutional interventions. Objective: This study aimed to evaluate the knowledge and compliance with standard precautions among nursing students. Methods: A cross-sectional study was conducted at the Lahore School of Nursing among 58 fifth-semester BSN students, selected from a population of 76 using Slovin’s formula and convenient sampling. Data were collected using a validated questionnaire adapted from Getachew study which included 19rekated to knowledge and 17 Likert-scale items on compliance. Knowledge and compliance were categorized into levels, and data were analysed using SPSS version 22. Descriptive statistics summarized participant characteristics, while Pearson’s correlation tested the association between knowledge and compliance (p ≤ 0.05). Results: The findings revealed that overall knowledge of standard precautions was relatively high, though gaps existed in specific areas such as nosocomial infections and hand hygiene. Compliance levels varied, with students demonstrating stronger adherence in some practices than others. A positive correlation was observed between knowledge and compliance, indicating that greater knowledge was associated with better adherence to standard precautions. Conclusion: While nursing students showed good knowledge of standard precautions, compliance required strengthening, particularly in critical areas. Educational interventions focusing on practical demonstrations, continuous reinforcement, and role modelling by educators are recommended to improve adherence and ensure patient and nurse safety.